Pengembangan Media Pembelajaran Interaktif Berbasis Android pada Mata Pelajaran Informatika Kelas VII di SMP Negeri 2 Kota Pontianak - Ferry Marlianto; Henny Puspitasari; Meli Hawani Septiani; Nia Naniati; Feronika Mila; Mursidarti; Kiki Rianti (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
The media act as a go-between for the person sending the word and the person receiving it. “Media” refers to the people, things, or events that work together to create a setting that helps students learn facts, skills, or attitudes. A Research and Development (R&D) methodology was used for this study. An R&D methodology is a set of activities or procedures that are used to make a new product or improve a current product so that it will persist in the future. The ADDIE development approach was used for the study, which combines the research and development (R&D) stages. To make learning plans for things, the ADDIE method is used. ADDIE stands for Analysis, Design, Development, Implementation, and Evaluation. What the study found the goal of making Android-based engaging learning materials for class VII Informatics topics at SMP Negeri 2 Pontianak City is to give students an interesting and useful way to learn. The Android operating system is based on a Graphical User Interface (GUI), which makes it easy for students to see how the system works on the outside. This makes using Android smartphones as teaching tools very helpful. Additionally, the portability and wide availability of Android tablets make it easy for students to access educational materials without being limited by time or space. The goal of making engaging learning materials about informatics for high school students in the seventh grade at SMP Negeri 2 Pontianak City is to make learning fun and useful. The Android operating system is based on a Graphical User Interface (GUI), which makes it easy for students to see how the system works on the outside. This makes using Android smartphones as teaching tools very helpful.